Best Management Practices in the Banking, Finance and Insurance Sector of Sri Lanka - Perera, Travis (Journal of Comparative International Management)

(untitled) (Management Futures, 1999)
This paper identifies and analyzes five best practices that were persistently present in the management of successful companies in the banking, financial and insurance sector in Sri Lanka.